Spectral and Spatial Quality assessment of IHS and Wavelet Based Pan-sharpening Techniques for High Resolution Satellite Imagery - DadrasJavan, Farzaneh; Samadzadegan, Farhad; Fathollahi, Fatemeh (European Journal of Applied Sciences, 2018)
Over last decades, a wide range of pan-sharpening methods have been proposed to synthesize images in a way that contain both high spatial and spectral characteristics of the multispectral and panchromatic images in high resolution satellite imagery. Amongst all improved methodologies, two different scenarios of Wavelet based and IHS based strategies brought up to be more appealing. Until now, lots of modifications and integrations are also proposed for these methods and variety of new techniques are presented. In this paper, the potential of different IHS-based and wavelet-based pan-sharpening techniques is studied and evaluated. For the purpose, high resolution images of worldview-2 satellite imagery are used and pan-sharpened images are generated based on 9 wavelet based and 6 IHS based methods. Achieved results clearly show the superiority of GIHS method as an optimum solution to keep both spectral and spatial characteristics if input images in fused image.